Chemical, Physical, and Technological Characteristics of Palm Olein and Canola Oil Blends - Ayman Younes Allam; Zakir Showkat Khan; Mohmad Sayeed Bhat; Bindu Naik; Sajad Ahmad Wani; Sarvesh Rustagi; Tahmeed Aijaz; Mohamed Farouk Elsadek; Tse-Wei Chen (Journal of Food Quality)
Because of the limited technical properties of their native forms, oils and fats are frequently blended to achieve the desired textural and oxidative properties. In this study, canola and palm oil blends were prepared in nine different proportions: B1 (90 : 10), B2 (80 : 20), B3 (70 : 30), B4 (60 : 40), B5 (50 : 50), B6 (40 : 60), B7 (30 : 70), B8 (20 : 80), and B9 (10 : 90). Pure palm oil (PO) and canola oil (CO) were used as the controls. All blends were assessed for physicochemical properties, fatty acid composition, heat treatment, and polymer content. The results indicated negative cold tests only for B1 and B2 blends with 10 and 20% PO, respectively. Iodine value decreased with increasing palm oil concentration and was lowest (62.03 ± 0.526) for blend B9, i.e., 90% PO. The fatty acid profile indicated more saturated fatty acids and a higher percentage of oleic acid in PO than in CO. The fatty acid profile values of blends B1–B9 were between those of the pure PO and CO. Linoleic and linolenic acids were more in blends B1–B9 than those in pure PO. The polymer content of PO (7.17%) was found to be lower than that of CO (10.32%) after 60 h of heating at 180°C. In addition, biologically active substances (BASs), which could be formed during the frying process, were tested by measuring the inhibition zone of E. coli growth. PO retarded BAS formation. The blended palm or canola oils resulted in better stability and increased organoleptic characteristics and hence can be suitable as economical and healthy alternatives to pure palm or canola oil.